ANALYSIS OF THE PRAGMALINGUISTIC CHARACTERISTICS OF PREMIUMS - Shamuratova, Malika (Журнал иностранных языков и лингвистики, 2023)
The emergence of pragma-linguistic features of premiums in our article will be presented in the following work. Pragmatic information, which is formed from the semantics of parameters according to communicative intention, arises in a specific communicative situation in the speech process or speaking and serves as linguistic and non-linguistic, historical-cultural, expressive and socio-economic information desired by the speaker. The evaluation of the object of communication is reflected in a positive, salba or neutral attitude towards beings, people, objects and phenomena, linguistic units that represent the characteristics of national, cultural, ethnic and social status in the linguistic perception of the world.